Totally disconnected compactifications - Parfeny P. Saworotnow (International Journal of Mathematics and Mathematical Sciences)
There is a one-to-one order preserving correspondence between totally disconnected compactifications of a topological space and certain Boolean algebras of open closed subsets on it.